The Importance of English to Promote 'Wisata Hemat Kebumen' Travel Agent on Online Media - Oktaviani, Nanda; Hadiningrum, Indriyati; puspitasari, indah (Jurnal Vokasia, 2022)
“Wisata Hemat Kebumen” Tour and Travel is a service provider engaged in tourism event organizers with the most halal tourism concept, effective, efficient and economical. WHK Tour and Travel has done promotions through social media, but only uses Indonesian. Therefore, the writer wants to make a promotion using English and through online media, namely Blog. The writer used the methods of observation, interviews, and documentation. Based on the results of the interview, the writer knows that this travel agency has a branch located in Karimunjawa with the name Wisata Hemat Karimunjawa. The writer also gets new experiences besides making promotions such as making departure schedules and being a tour leader. In making the promotional text, the writer did several stages, namely creating a blog with the director of WHK Tour and Travel, choosing a tour package to be uploaded, namely a special tour package for companies, then grouping tour packages by province so that it is easier for consumers to choose the tour package. After all the information has been collected, the writer then arranges the information and translates it into English. The writer submits the results of the writing to the director of WHK Tour and Travel to be corrected and after obtaining approval then the article is uploaded through the official blog of WHK Tour and Travel. There were several obstacles when the writer made promotions such as, WHK was being less helpful to the writer in carrying out job training, lacks of understanding of English from WHK Tour and Travel, and WHK Tour and Travel of does not yet have a website. To overcome this, the writer looks for information on all social media WHK Tour and Travel and other websites, uses several applications to improve grammar, namely Google Docs and Grammarly, and creates a new website, namely Blog.